2016
DOI: 10.1111/tbed.12538
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Evaluation of a Real-Time PCR Assay on a Portable Instrument as a Possible Field Diagnostic Tool: Experiences from the Testing of Clinical Samples for African and Classical Swine Fever Viruses

Abstract: African swine fever (ASF) and classical swine fever (CSF) are two highly infectious transboundary animal diseases (TADs) that are serious threats to the pig industry worldwide, including in China, the world's largest pork producer. In this study, a duplex real-time PCR assay was developed for the rapid detection and differentiation of African swine fever virus (ASFV) and classical swine fever virus (CSFV). The assay was performed on a portable, battery-powered PCR thermocycler with a low sample throughput (ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Recently, field applicable RT-PCRs [184] but also alternatives have been designed such as loop-mediated isothermal amplification (LAMP) assays [185,186,187,188,189,190], primer-probe energy transfer RT-qPCR [191,192] or recently insulated isothermal RT-qPCR [193]. Moreover, CSFV can be isolated on different permanent cell lines such as porcine kidney cell lines PK15 or SK6 (Technical Annex to Commission Decision 2002/106/EC).…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, field applicable RT-PCRs [184] but also alternatives have been designed such as loop-mediated isothermal amplification (LAMP) assays [185,186,187,188,189,190], primer-probe energy transfer RT-qPCR [191,192] or recently insulated isothermal RT-qPCR [193]. Moreover, CSFV can be isolated on different permanent cell lines such as porcine kidney cell lines PK15 or SK6 (Technical Annex to Commission Decision 2002/106/EC).…”
Section: Diagnosismentioning
confidence: 99%
“…Concordant results were obtained showing a good consistency between the two nucleic acids extraction methods (Table S1). Previous studies have demonstrated a slightly better performance of the bead-based protocol (Liu et al, 2017). Further application of the protocol to process the 64 blood samples that had been collected during previous outbreak investigations, demonstrated the practicability and ease of performing the protocol at NADDEC.…”
Section: Resultsmentioning
confidence: 95%
“…The use of a commercial battery-powered portable thermocycler (T-COR 4 TM ) for the detection of ASFV via a real-time PCR assay has previously been evaluated (174,175). In one study, reduced sensitivity of the portable thermocycler for clinical samples with very high Ct values on the gold standard qPCR was observed on a RT-PCR/PCR duplex assay for Classical and African swine fever viruses (175).…”
Section: Molecular Detection Of Asfv Dnamentioning
confidence: 99%
“…The use of a commercial battery-powered portable thermocycler (T-COR 4 TM ) for the detection of ASFV via a real-time PCR assay has previously been evaluated (174,175). In one study, reduced sensitivity of the portable thermocycler for clinical samples with very high Ct values on the gold standard qPCR was observed on a RT-PCR/PCR duplex assay for Classical and African swine fever viruses (175). In our hands, portable thermocyclers (e.g., GeneReach Pockit TM or Biomeme Franklin TM ) show comparable clinical and analytical sensitivity and specificity using ASF positive and negative experimental and field samples when compared to a laboratory thermocycler (Bio-Rad CFX 96).…”
Section: Molecular Detection Of Asfv Dnamentioning
confidence: 99%